Group 2 Innate Lymphoid Cells Participate in Renal Fibrosis in Diabetic Kidney Disease Partly via TGF-β1 Signal Pathway. (3rd July 2019) - Liu, Cuiping; Qin, Ludan; Ding, Jingya; Zhou, Luping; Gao, Chenlin; Zhang, Ting; Guo, Man; Huang, Wei; Jiang, Zongzhe; Long, Yang; Xu, Yong
Abstract : Aim . To explore the role of group 2 innate lymphoid cells (ILC2s) in the pathogenesis of renal fibrosis in diabetic kidney disease (DKD). Methods . The proportion of ILC2s and the levels of Th2 cytokines (IL-4, IL-5, and IL-13) in the peripheral blood of normal control subjects (NC) or patients with type 2 diabetes mellitus (DM), early diabetic kidney disease (DKD1), or late diabetic kidney disease (DKD2) were analyzed by flow cytometry and ELISA. The expression of transforming growth factor- β 1 (TGF- β 1), fibronectin (FN), collagen1, IL-4R α, and IL-13R α 1 in renal tubular epithelial cells (HK-2) induced by IL-4, IL-13, or high glucose was analyzed by ELISA or qPCR. Results . The proportion of ILC2s and the levels of IL-4, IL-5, and IL-13 were significantly increased in DKD patients and were positively correlated with the severity of DKD (P < 0.05 ). The expression of TGF- β 1, FN, and collagen1 was significantly upregulated in HK-2 cells induced by IL-4 or IL-13 (P < 0.05 ). Moreover, the IL-4R α and IL-13R α 1 mRNA in HK2 cells were increased followed by high glucose alone or combined with IL-4 or IL-13, but the differences were not statistically significant (P > 0.05 ). However, compared with high-glucose stimulation alone, the expression of TGF- β 1, FN, and collagen1 was significantly increased in HK-2 cells induced by high glucose combined with IL-4 or IL-13 (P < 0.05 ). Conclusions . ILC2s may participate in renal fibrosis in DKD partly via TGF- β 1 signal pathway.